2015
DOI: 10.3171/2015.3.spine14743
|View full text |Cite
|
Sign up to set email alerts
|

Impact of obesity on complications, infection, and patient-reported outcomes in adult spinal deformity surgery

Abstract: OBJECT Adult spinal deformity (ASD) surgery is known for its high complication rate. This study examined the impact of obesity on complication rates, infection, and patient-reported outcomes in patients undergoing surgery for ASD. METHODS This study was a retrospective review of a multicenter prospective database of patients with ASD who were treated surgically. Patients with available 2-year follow-up d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 96 publications
(55 citation statements)
references
References 81 publications
0
54
0
1
Order By: Relevance
“…15 Another study, by Ayhan et al, also revealed that in 121 patients who underwent adult deformity correction, a total of 114 complications (59 major, 55 minor) and 1 death were noted. 5 At Level II evidence there is significant quality of life improvement, 20 and with complications, the final outcome of radiological correction did not change. 19 So unless there are strong indications to undertake deformity correction surgery, smaller procedures aiming to provide symptomatic relief from radicular pain may be worth considering.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…15 Another study, by Ayhan et al, also revealed that in 121 patients who underwent adult deformity correction, a total of 114 complications (59 major, 55 minor) and 1 death were noted. 5 At Level II evidence there is significant quality of life improvement, 20 and with complications, the final outcome of radiological correction did not change. 19 So unless there are strong indications to undertake deformity correction surgery, smaller procedures aiming to provide symptomatic relief from radicular pain may be worth considering.…”
Section: Discussionmentioning
confidence: 87%
“…6 Every "redo" spine surgery in itself is quite complicated, and more so when it is performed in the elderly population. 20 Addressing the entire spine as a single unit enables the surgeon to plan the possible future procedures with minimal complications. 13,25 Endoscopic discectomy enables the preservation of all the essential structures with minimal complications, although there is a steep learning curve for beginners.…”
Section: Discussionmentioning
confidence: 99%
“…1,10,14 While most studies have revealed either a higher complication rate or increased resource utilization, inferior clinical outcomes in obese patients have not been consistently demonstrated. 14,28 Despite the current lack of evidence, a tendency to favor less extensive, nonfusion procedures in obese patients is plausible given the historically higher postoperative complication rates associated with these patients. One possible reason for these higher rates could be that patients with higher BMIs are at risk for longer and more technically difficult procedures.…”
mentioning
confidence: 99%
“…26 Machino et al in two different papers, one 505 patients, the other 105 patients that underwent double-door laminoplasty for CSM, found worse pre-and post-operative Japanese Orthopaedic Assocaition ( JOA) scores, and slower, reduced improvement in patients with diabetes >10 years and HgbA1C>6.5%. 17,27 Dokai et al reported that, among CSM patients treated with ex- Table 3. Multivariate analysis for impact of diabetes on intra-and peri-operative patient outcomes.…”
Section: Discussionmentioning
confidence: 99%